SCIENTIFIC AND THEORETICAL ASPECTS OF THE DEVELOPMENT OF FOOD ENTERPRISES IN GLOBAL COMPETITION (Marketing Journal, 2025)
The article summarizes the main elements of the evaluation system for key performance indicators of food service enterprises and examines the role of such assessment. Special attention is given to the development of food service as a platform for the susta inable growth of trade and the national economy. It is substantiated that food service enterprises, due to their characteristics, belong to complex socio -economic systems, and proposals for the development of the sector have been formulated.
Keywords: food service; food service enterprises; types of food service enterprises; national economy; synergistic efficiency